Increased BK Viremia and Progression to BK-Virus Nephropathy Following High-Dose Intravenous Immunoglobulin for Acute Cellular Rejection. Issue 6 (1st June 2014) - Boonyapredee, Maytee; Knight, Kendral; Little, Dustin
ABSTRACT: BK virus nephropathy and cellular rejection are common causes of allograft dysfunction in renal transplant recipients. The two can be difficult to distinguish on allograft biopsy and can be present simultaneously. Management of the patient with coexistent BK infection and rejection is complicated by the conflicting ideals of decreasing immunosuppression to treat the former and increasing immunosuppression to treat the latter. The authors present the case of a 57-year-old renal transplant recipient who underwent allograft biopsy 8 weeks post-transplant for evaluation of increased serum creatinine in the setting of BK viremia (BKV). Biopsy revealed Banff classification 1b acute cellular rejection, with insufficient evidence to diagnose BK virus-associated nephropathy. The patient was administered intravenous immune globulin (IVIG), with no other changes in immunosuppressive therapy. Plasma and urine BK increased exponentially following IVIG administration, and allograft function further deteriorated. Repeat biopsy showed overt BK viral nephropathy, and BKV and creatinine decreased only after reduction in immunosuppression and initiation of leflunomide. Although case series have suggested a potential role for IVIG in the setting of BK infection, further study is needed to define the safety and efficacy of this approach.